2002
DOI: 10.1038/sj.jim.7000320
|View full text |Cite
|
Sign up to set email alerts
|

Chloroxylenol- and triclosan-tolerant bacteria from industrial sources

Abstract: Potential development of bacterial tolerance to biocides in the industrial environment is examined in this study. Bacteria tolerant to the phenolic-type agent para-chloro-meta-xylenol (PCMX) and the bis-phenol 2,4,4'-trichloro-2'-hydroxydiphenylether (triclosan) were isolated from industrial sources and identified. Minimum inhibitory concentrations (MICs) were determined and compared with those of culture collection (standard) strains. Of around 100 isolates originally obtained, most were naturally tolerant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…One recent cross-sectional study ( 17 ) reported a higher prevalence of decreased susceptibility to triclosan among methicillin-resistant S. epidermidis compared to methicillin-sensitive S. epidermidis clinical isolates. The findings reported in other cross-sectional studies have mainly examined environmental and clinical isolates of bacteria, and the correlations reported have been inconsistent ( 11 , 13 , 18 20 ). …”
Section: Discussionmentioning
confidence: 90%
“…One recent cross-sectional study ( 17 ) reported a higher prevalence of decreased susceptibility to triclosan among methicillin-resistant S. epidermidis compared to methicillin-sensitive S. epidermidis clinical isolates. The findings reported in other cross-sectional studies have mainly examined environmental and clinical isolates of bacteria, and the correlations reported have been inconsistent ( 11 , 13 , 18 20 ). …”
Section: Discussionmentioning
confidence: 90%
“…Field studies have provided some evidence for reduced susceptibility to certain disinfectants among bacterial isolates from hatcheries (where disinfectants are applied daily, usually at sublethal concentrations) and biocide manufacturing plants (Lear, Maillard, Dettmar, Goddard, & Russell, 2002;Willinghan, Sander, Thayer, & Wilson, 1996). However, other studies (examining farm bacteria) have failed to find significant evidence of such associations (Aarestrup & Hasman, 2004;Martin & Maris, 1995).…”
Section: Co-selection Of Amr By Disinfectantsmentioning
confidence: 99%
“…There are growing concerns over the toxicological effects of the exposure of these compounds to humans and the ecosystem . The identified risks include development of microbial resistance to antibiotics and feminization or masculinization of aquatic organisms on exposure to hormones , among others. The environmental compartments that have been studied include wastewater treatment plant (WWTP) influents, effluents, and receiving surface water ; sediments ; biosolids and waste from confined animal farms ; and groundwater and drinking water .…”
Section: Introductionmentioning
confidence: 99%